Reducing inequities in maternal and child health in rural Guatemala through the CBIO+ Approach of Curamericas: 6. Management of pregnancy complications at Community Birthing Centers (Casas Maternas Rurales) - Elijah T. Olivas; Mario Valdez; Barbara Muffoletto; Jacqueline Wallace; Ira Stollak; Henry B. Perry (BMC, 2023)
Background In Guatemala, Indigenous women have a maternal mortality ratio over twice that of non-Indigenous women. Long-standing marginalization of Indigenous groups and three decades of civil war have resulted in persistent linguistic, economic, cultural, and physical barriers to maternity care. Curamericas/Guatemala facilitated the development of three community-built, -owned, and -operated birthing centers, Casas Maternas Rurales (referred to here as Community Birthing Centers), where auxiliary nurses provided physically accessible and culturally acceptable clinical care. The objective of this paper is to assess the management of complications and the decision-making pathways of Birthing Center staff for complication management and referral. This is the sixth paper in the series of 10 articles. Birthing centers are part of the Expanded Census-based, Impact-oriented Approach, referred to as CBIO+. Methods We undertook an explanatory, mixed-methods study on the handling of pregnancy complications at the Birthing Centers, including a chart review of pregnancy complications encountered among 1,378 women coming to a Birthing Center between 2009 and 2016 and inductively coded interviews with Birthing Center staff. Results During the study period, 1378 women presented to a Birthing Center for delivery-related care. Of the 211 peripartum complications encountered, 42.2% were successfully resolved at a Birthing Center and 57.8% were referred to higher-level care. Only one maternal death occurred, yielding a maternal mortality ratio of 72.6 maternal deaths per 100,000 live births. The qualitative study found that staff attribute their successful management of complications to frequent, high-quality trainings, task-shifting, a network of consultative support, and a collaborative atmosphere. Conclusion The Birthing Centers were able to resolve almost one-half of the peripartum complications and to promptly refer almost all of the others to a higher level of care, resulting in a maternal mortality ratio less than half that for all Indigenous Guatemalan women. This is the first study we are aware of that analyzes the management of obstetrical complications in such a setting. Barriers to providing high-quality maternity care, including obtaining care for complications, need to be addressed to ensure that all pregnant women in such settings have access to a level of care that is their fundamental human right.